Heat transfer variations of bicycle helmets - Brühwiler, P. A.; Buyan, M.; Huber, R.; Bogerd, C. P.; Sznitman, J.; Graf, S. F.; Rösgen, T. (Journal of Sports Sciences, 2006)
Bicycle helmets exhibit complex structures so as to combine impact protection with ventilation. A quantitative experimental measure of the state of the art and variations therein is a first step towards establishing principles of bicycle helmet ventilation. A thermal headform mounted in a climate-regulated wind tunnel was used to study the ventilation efficiency of 24 bicycle helmets at two wind speeds. Flow visualization in a water tunnel with a second headform demonstrated the flow patterns involved. The influence of design details such as channel length and vent placement was studied, as well as the impact of hair. Differences in heat transfer among the helmets of up to 30% (scalp) and 10% (face) were observed, with the nude headform showing the highest values. On occasion, a negative role of some vents for forced convection was demonstrated. A weak correlation was found between the projected vent cross-section and heat transfer variations when changing the head tilt angle. A simple analytical model is introduced that facilitates the understanding of forced convection phenomena. A weak correlation between exposed scalp area and heat transfer was deduced. Adding a wig reduces the heat transfer by approximately a factor of 8 in the scalp region and up to one-third for the rest of the head for a selection of the best ventilated helmets. The results suggest that there is significant optimization potential within the basic helmet structure represented in modern bicycle helmets.